Pengaruh Pembangunan Infrastruktur Jalan Tani Terhadap Kesejahteraan Masyarakat Di Desa Lauwa Kecamatan Pitumpanua Kabupaten Wajo - Mastura Karateng; Mulyadi Mulyadi; Masweni Masweni (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
The background of this research is that road infrastructure development activities, especially farm roads, have great potential to have an impact that will affect the level of welfare of the village community. And with the construction of this farm road infrastructure, it is a transportation infrastructure in agricultural areas, to facilitate the mobility of agricultural tools and machinery. Transporting production facilities to agricultural land and transporting agricultural products from land to storage areas, processing areas or markets. This study aims to examine the effect of Farmer Road Infrastructure Development on Community Welfare in Lauwa Village, Pitumpanua District, Wajo Regency. This research uses quantitative research methods. The population in this study were all farmers in Lauwa Village, Pitumpanua District, Wajo Regency, as many as 350 people. The sample in this study used a probability sampling technique with a simple random sampling type, while the sample size was obtained from calculations using the Slovin formula with an error rate of 10% from 78 people. . The primary data source is in the form of a questionnaire. The data analysis technique used is descriptive statistical analysis, correlation analysis, coefficient of determination, simple linear regression analysis. Questionnaire measurements answered by respondents used a Likert scale which was processed using Statistical Product and Service Solution (SPSS). The results of this study indicate that Jalan Tani Infrastructure Development has a positive and significant impact on the welfare of the people in Lauwa Village, Pitumpanua District, Wajo Regency. While the value of R2 (R Square) is 0.081 which indicates that the contribution of the Farmer Road Infrastructure Development variable to the community welfare variable in Lauwa Village, Pitumpanua District, Wajo Regency is 8.10%.